2020
DOI: 10.5812/jkums.99914
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Binaural Beat Music on Reducing Anxiety and Pain and Increasing Satisfaction of Ophthalmic Patients

Abstract: Background: Preoperative anxiety can reduce the quality of anesthesia and increase the need for anesthetic medications, which can inadvertently increase the length of anesthesia and delay awakening, which results in more complications of anesthesia and surgery. Objectives: The purpose of this study is to investigate the effect of binaural beat music (BBM) on anxiety, pain and satisfaction of patients with eye surgery. Methods: This clinical trial enrolled sixty patients presenting to the surgical unit of Imam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…Similarly, this study is concordant with studies by Padmanabhan et al [ 7 ] and Roshani et al [ 13 ], who proved that binaural tone music has significant potential to reduce preoperative anxiety and pain, thus maintaining hemodynamic parameters. On comparing intraoperative mean arterial pressure (MAP) and pulse rates between binaural tone music and the midazolam group, MAPs were significantly lower in binaural tone music at different time points.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, this study is concordant with studies by Padmanabhan et al [ 7 ] and Roshani et al [ 13 ], who proved that binaural tone music has significant potential to reduce preoperative anxiety and pain, thus maintaining hemodynamic parameters. On comparing intraoperative mean arterial pressure (MAP) and pulse rates between binaural tone music and the midazolam group, MAPs were significantly lower in binaural tone music at different time points.…”
Section: Discussionsupporting
confidence: 92%
“…In current study, it was found that all participants (between 45-80) were with high pre-operative anxiety levels whereas, studies conducted in Pakistan [30], Thailand [31], Turkey [32] and Italy [33] showed most of their participants (between 35 to 80)were with moderate to high anxiety levels. In this study, it was found that most of the patients belong to age group between the 30 to 70 years, which is supported by a studies conducted in Thailand [31,34], and Iran [35]. In this study, both binaural beats and counseling techniques showed a statistically significant reduction in pre-operative anxiety levels among CABG patients but binaural beat music reduced more effectively then the counseling technique.…”
Section: Discussionsupporting
confidence: 68%
“…Patients in the BB group showed significant reductions in blood pressure and anxiety. Roshani et al (2019) investigated the effect of BB with music on anxiety and pain of patients prior to eye surgery. Post-surgical anxiety and pain were significantly lower in the BB group than in the control group.…”
Section: Introductionmentioning
confidence: 99%